If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 + 5x = 2x + 6 + 14 Reorder the terms: -12 + 3x + 5x = 2x + 6 + 14 Combine like terms: 3x + 5x = 8x -12 + 8x = 2x + 6 + 14 Reorder the terms: -12 + 8x = 6 + 14 + 2x Combine like terms: 6 + 14 = 20 -12 + 8x = 20 + 2x Solving -12 + 8x = 20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 8x + -2x = 20 + 2x + -2x Combine like terms: 8x + -2x = 6x -12 + 6x = 20 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 6x = 20 + 0 -12 + 6x = 20 Add '12' to each side of the equation. -12 + 12 + 6x = 20 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 20 + 12 6x = 20 + 12 Combine like terms: 20 + 12 = 32 6x = 32 Divide each side by '6'. x = 5.333333333 Simplifying x = 5.333333333
| 2x^2+4x-837=0 | | 6x^4-3=-7x^2 | | C=4uv | | -8/-36 | | 3x+6x+9x= | | 172=21x+25 | | 12x+0(15)=.07(x+15) | | 3(x+1)=3+6x | | 6(3x+2)+3(3x-1)= | | 4(d-3)=2d+4d-5 | | 14+27x=20x+35 | | 2x+16y=-9 | | A+b-18=206 | | 7(-4w-12)=28 | | 42w/36x=! | | 3(2t+4)+4(3t-3)= | | 181=10x+11 | | 3(x+2)-(x-5)=0 | | -4-2x=-2(x-2) | | x+0.06x=42.40 | | 12m=42 | | 15-2z=31 | | b+9=29 | | -2/3•n=12 | | 1.6(2c+12)=12 | | 46-4x=16+11x | | 2(6c-2)+8c+6= | | 64-48= | | X^2y^4-81x^2=0 | | fx=9 | | 14x-8+6x=6(5x-3)+5 | | 11(k-1)=7(k-0.25) |